2022
DOI: 10.1039/d1ob02284a
|View full text |Cite
|
Sign up to set email alerts
|

Rongalite-induced transition-metal and hydride-free reductive aldol reaction: a rapid access to 3,3′-disubstituted oxindoles and its mechanistic studies

Abstract: A transition-metal and hydride-free reductive aldol reaction has been developed for the synthesis of biologically active 3,3´-disubstituted oxindoles from isatin-derivatives using rongalite. In this protocol, rongalite plays the dual role...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Based on the existing literature 31,35,36 and collected information, a full mechanistic proposal is summarized in Scheme 4. Firstly, 2-oxindole reacts with in situ generated formaldehyde from rongalite under basic conditions to form intermediate ( I ), which further undergoes dehydration to yield intermediate 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the existing literature 31,35,36 and collected information, a full mechanistic proposal is summarized in Scheme 4. Firstly, 2-oxindole reacts with in situ generated formaldehyde from rongalite under basic conditions to form intermediate ( I ), which further undergoes dehydration to yield intermediate 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Although there are several variations of RAR, metal and hydride-free RARs have been attracting chemists from all over the world in recent years. 33 In continuation of our efforts on exploring the synthetic utility of rongalite 34 and reductive aldol reactions (Scheme 1c), 35 herein, we report a domino aldol condensation reaction followed by the transition metal and hydride-free reductive aldol reaction to synthesize 3-(hydroxymethyl)-3-methylindolin-2-ones using multifaceted rongalite as the reducing agent and double C1 unit donor.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the same research group has reported a transition‐metal as well as hydride‐free reductive aldol reaction for the preparation of various bio‐active 3,3′‐disubstituted oxindole derivatives (79–96 % yields) from isatins with the involvement of an inexpensive and easily assessable rongalite ( ca . $0.03/1 g) [45] . Herein, the rongalite played a double role both as C1 ‐unit donor and a hydride‐free reducing agent.…”
Section: Synthesis Of 33′‐disubstituted Oxindoles Via Reductive Aldol...mentioning
confidence: 99%
“…By utilizing sodium sulfide/rongalite, only symmetrical sulfides 16 /sulfones 17 are prepared from halides and these reagents are further explored. 18 Sodium hydrosulfide (NaHS), highly hygroscopic and difficult to handle, is a source for HS − which leads to the formation of thiols and hence adding one more step towards preparing sulfides. 19 KSCN leads to thiocyanate products as well as isothiocyanate products.…”
Section: Introductionmentioning
confidence: 99%